Complementary or Substitutive Environmental Governance? ISO 14001 and Environmental Stringency for Emission Reduction - Margaret, Irene; Surroca, Jordi A.; Tribó, Josep A. (Journal of Management Studies, 2026)
Abstract In this paper, we adopt the so‐called ‘related’ perspective on business and government relations and propose that they interact and influence one another in governing corporate responsibility. We theorize that private and public governance may operate as complements or substitutes, and conduct a comparative institutional analysis to identify the institutional systems under which each form of interaction prevails. To illustrate our conceptual framework, we use the global diffusion of ISO 14001 as an indicator of the growing privatization of environmental governance and environmental stringency as a reflection of the strength and effectiveness of public environmental governance. Then, we empirically examine how ISO 14001 and environmental stringency interact to reduce corporate emissions across varieties of institutional systems. Contrary to the dominant view that public and private governance are substitutes, we propose that they can complement one another, depending on the institutional setting. Our results show that complementarity is more likely when the institutional systems follow a market‐based logic, such as in the liberal market economies, and when firms expand internationally. This finding holds after using alternative methodological approaches and more granular classifications of institutional systems. We discuss implications for governance research in management studies and practical implications for tackling grand environmental challenges.